Development of an innovative virtual reality training system and its effect on mental training in gymnasts - Sato, Y.; Fukami, M.; Endo, K.; Mizushima, K.; Nishikawa, D.; Takayose, M.; Koshizawa, R. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION Research on the use of virtual reality (VR) for mental training in athletes is increasing. VR can simulate situations that athletes may not usually experience, including unusual competition scenarios and environments such as stadiums the athletes have not visited before. We have been developing an innovative VR training system (iVRTS) and have used it for mental training to enhance athlete performance. Users wear a head-mounted display (HMD) and can move freely in a VR environment constructed based on an actual stadium. However, it is unclear whether the iVRTS is effective for mental training, such as performing breathing techniques while experiencing a simulated stressful situation. Therefore, this study aimed to assess the effectiveness of iVRTS for mental training by analysing biometric information.